COMPARISON OF DATA PROTECTION POLICIES IN EUROPE AND THE UNITED STATES: DIFFERENT LEGAL APPROACHES - Era Purike; Loso Judijanto (ADISAM PUBLISHER, 2025)
This comparative analysis reveals fundamental differences between data protection policies in Europe and the United States, which stem from different legal approaches. In Europe, the General Data Protection Regulation (GDPR) provides a strict and centralised framework for protecting individual privacy rights, with an emphasis on individual control over their personal data. In contrast, the United States takes a more fragmented approach, with regulations varying across sectors and states, such as the Health Insurance Portability and Accountability Act (HIPAA) and the California Consumer Privacy Act (CCPA). The US approach is more oriented towards trade and data security aspects than individual privacy rights. This difference reflects varying policy priorities, with Europe focusing more on privacy protection and the US emphasising economic and innovation aspects. Going forward, global challenges require cross-border cooperation and policy adaptation to balance the need for data protection, business and technological development